Effectiveness of Dual Focus Mutual Aid for Co-occurring Substance Use and Mental Health Disorders: A Review and Synthesis of the “Double Trouble” in Recovery Evaluation - Magura, Stephen (2008)
Over five million adults in the U.S. have a co-occurring substance use disorder and serious psychological distress. Mutual aid (“self-help”) can usefully complement treatment, but people with co-occurring substance use and psychiatric disorders often encounter a lack of empathy and acceptance in traditional mutual aid groups. Double Trouble in Recovery (DTR) is a dual focus fellowship whose mission is to bring the benefits of mutual aid to persons recovering from co-occurring disorders. An evaluation of DTR was conducted by interviewing 310 persons attending 24 DTR meetings in New York City in 1998 and following them up for two years, in 1999 and 2000. The evaluation produced 13 articles in 12 peer reviewed journals, the main results of which are summarized here. The sample’s characteristics were: mean age, 40 years; women, 28%; black, 59%; white, 25%; Hispanic, 14%; never married, 63%; live in supported community residence, 53%; high school graduate or GED, 60%; arrested as adult, 63%; diagnoses of: schizophrenia, 39%; major depression, 21%; or bipolar disorder; 20%; currently prescribed psychiatric medication, 92%; primary substance used, current or past: cocaine/crack, 42%; alcohol 34%; or heroin, 11%. Overall, the findings indicate that DTR participation has both direct and indirect effects on several important components of recovery: drug/alcohol abstinence, psychiatric medication adherence, self-efficacy for recovery, and quality of life. The study also identified several “common” therapeutic factors (e.g., internal motivation, social support) and unique mutual aid processes (helper-therapy, reciprocal learning) that mediate the influence of DTR participation on recovery. For clinicians, these results underline the importance of fostering stable affiliation with specialized dual focus 12-step groups for their patients with co-occurring disorders, as part of a comprehensive recovery-oriented treatment approach.